Author Correction: Kilohertz frame-rate two-photon tomography - Kazemipour, Abbas; Novak, Ondrej; Flickinger, Daniel; Marvin, Jonathan S; Abdelfattah, Ahmed S; King, Jonathan; Borden, Philip M; Kim, Jeong Jun; Al-Abdullatif, Sarah H; Deal, Parker E; Miller, Evan W; Schreiter, Eric R; et al. (Nature methods, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.